ANALISIS COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN OBJEK WISATA ALAS KEDATON MONKEY FOREST KABUPATEN TABANAN - Ni Kadek Intan Dwi Agustini; Agung Yuli I Gusti Agung Ayu Yuliartika Dewi; Nyoman Sumawidayani (Kebijakan : Jurnal Ilmu Administrasi, 2026)
Tourism is an important sector in economic development, especially in areas that have natural and cultural potential such as Bali. Alas Kedaton Monkey Forest, as one of the natural tourist attractions in Tabanan Regency, faces challenges in its management, especially related to its natural and cultural potential.Tabanan, faces challenges in its management, especially related to the decline in the number of tourist visits after the COVID-19 pandemic. This problem is exacerbated by low community participation, lack of collaboration with the private sector, and not optimal collaboration-based management. This research focuses on analyzing the application of collaborative governance in the development of the Alas Kedaton Monkey Forest Tourism Object, with an emphasis on collaboration between the Kukuh Customary Village, the private sector, and the Kukuh Village community. The purpose of this research is to understand the collaborative governance process that occurs and identify the impact of the collaboration on the development of tourist attractions. This research used a qualitative approach with descriptive methods. Research informants were determined using purposive sampling technique. The number of informants in this study were eight people, consisting of the Head of Kukuh Village, tourism object managers, private sector parties (PT. Pertamina Fuel Terminal Sanggaran), Pokdarwis members, Kukuh Village community, and visitors to Alas Kedaton Monkey Forest. This research uses data analysis techniques of Miles and Huberman's interactive analysis model which includes data reduction, data presentation, and conclusion drawing. Data collection techniques were carried out through observation, interviews, and documentation. The collaboration has succeeded in improving tourist facilities, improving infrastructure, and opening employment opportunities for local communities. However, community involvement is still limited and private sector contributions still need to be increased. This study recommends the need to strengthen communication between stakeholders and optimize digital-based promotion strategies to encourage the sustainability of the development of Alas Kedaton Monkey Forest. Keywords: Collaborative Governance, Tourism Site Development, Objek Wisata Alas Kedaton Monkey Forest